Looking back on the London Olympics: Independent outcome and hindsight effects in decision evaluation. (21st May 2015) - Blank, Hartmut; Diedenhofen, Birk; Musch, Jochen
Abstract : Outcome bias and hindsight bias are related, but how exactly? To remedy theoretical ambiguity and non‐existent directly relevant empirical research, we contrast an older idea (Baron & Hershey, 1988, J . Pers . Soc . Psychol ., 54, 569) that sees outcome bias as partly mediated through hindsight bias with the idea that the two biases independently affect decision evaluations. In an Internet study of retrospections on the 2012 London Olympics, evaluations of the Games' success and its foreseeability had independent effects on evaluations of the International Olympic Committee's decision to award the Olympics to London; there was no evidence of mediation. Further theoretical discussion emphasizes the need to distinguish between a holistic assessment of decisions and a more specific assessment of the decision‐making process in future outcome bias research.